1997
DOI: 10.1152/ajprenal.1997.272.3.f283
|View full text |Cite
|
Sign up to set email alerts
|

Low NO concentrations inhibit osteoclast formation in mouse marrow cultures by cGMP-dependent mechanism

Abstract: High concentrations of nitric oxide (NO) inhibit bone resorption by mature osteoclasts. We examined the effects of low NO concentrations on osteoclast formation in mouse bone marrow cultures. The NO releasers sodium nitroprusside (SNP) and S-nitroso-N-acetyl-DL-penicillamine inhibited the formation of multinucleated cells expressing tartrate-resistant acid phosphatase (a marker for osteoclasts) when administered during the last 3 days of 6-day cultures (differentiation stage) but not during the first 3 days (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 0 publications
4
35
1
1
Order By: Relevance
“…Whether this NO causes the reduction in c-Fos protein or whether c-Fos declines in an NO-independent manner is a subject for future inquiry. In previous work, NO (supplied by an exogenous NO donor) was reported to diminish OC formation via a cGMP-dependent mechanism in 1,25-dihydroxyvitamin D 3 -differentiated murine marrow cultures (11). In contrast, no evidence was obtained here for the involvement of a cGMP-dependent mechanism to mediate the inhibitory actions of endogenously stimulated iNOS-derived NO in RANKL-differentiated murine RAW cells.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Whether this NO causes the reduction in c-Fos protein or whether c-Fos declines in an NO-independent manner is a subject for future inquiry. In previous work, NO (supplied by an exogenous NO donor) was reported to diminish OC formation via a cGMP-dependent mechanism in 1,25-dihydroxyvitamin D 3 -differentiated murine marrow cultures (11). In contrast, no evidence was obtained here for the involvement of a cGMP-dependent mechanism to mediate the inhibitory actions of endogenously stimulated iNOS-derived NO in RANKL-differentiated murine RAW cells.…”
Section: Discussioncontrasting
confidence: 57%
“…This negative feedback pathway involves RANKL induction of interferon (IFN)-␤ in a c-Fos-dependent manner, followed by IFN-␤ inhibition of RANKL-induced c-Fos expression necessary for OC formation (5). OC formation and bone resorption are also inhibited by elevated levels of the multifunctional signal molecule nitric oxide (NO) in vivo and in vitro (7)(8)(9)(10)(11)(12)(13). NO is produced from L-arginine in an oxidative reaction catalyzed by NO synthase isoenzymes that are either constitutively expressed and calcium-activated (endothelial and neuronal NO synthase isoforms) or transcriptionally induced (inducible NO synthase (iNOS) isoform) in response to inflammatory stimuli (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, monocyte differentiation in the presence of adenylyl cyclase agonists such as PGE 2 (14)(15)(16) or the guanylyl cyclase agonist atrial natriuretic factor (ANF) (17) can polarize dendritic cells toward promoting Th1 or Th2 responses, respectively. Likewise, generation of osteoclasts from bone marrow precursors is potentiated by treatments that increase either cAMP or cGMP such as PGE 2 (18,19) and nitric oxide (20). Finally, differentiation of monocyte cell lines, such as the HL-60 (21-23) and U937 (24,25) lines, can be initiated by increased cAMP or cGMP levels.…”
mentioning
confidence: 99%
“…Moreover, deficient iNOS (van't Hof et al, 2000) mice showed an inhibition of osteoclastic functional activity, while eNOS knockout mice showed an impaired osteoblast function (Aguirre et al, 2001). Insufficient cellular NO concentration reduced consistently osteoclast differentiation from mouse bone marrow cells (Holliday et al, 1997), while other study reported that NO induced a reduction of osteoclast formation (van't Hof and . In order to get over these contradictions, some authors have recently proposed an interesting explanation of these studies suggesting that low-intermediate levels of NO induce osteoclast activity and survival while either the absence or the excess of NO inhibits osteoclast activation and survival (Brandi et al, 1995).…”
Section: Discussionmentioning
confidence: 87%